2010
DOI: 10.1590/s1519-69842010000100009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest fragmentation on dipterofauna (Calliphoridae) at the Reserva Biológica do Tinguá, Nova Iguaçu, RJ

Abstract: Samples were collected every month in three different sites of the Reserva Biológica do Tinguá, Brazil: site A was located on the border of the forest and sites B and C were located 1,000 and 500 m, respectively, towards the forest interior. The objective was to determine edge effects on a fragment of the Atlantic Forest. The greatest species richness was observed in sites A and B (23 species), compared with site C (16 species). Site A showed the greatest abundance and constancy, independent of the degree of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
4
16
0
5
Order By: Relevance
“…Point C was the most diverse (H'=1.843, J'=0.7687), followed by B (H'=1.382, J'=0.5387) and A (H'=0.926, P=0, 3612). These results are in agreement with those of Ferraz et al (2010b), who also found greater diversity in the farthest point from the edge (1,000m), and are also corroborated by the studies of Esposito (1999) in the Amazon, who found …”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Point C was the most diverse (H'=1.843, J'=0.7687), followed by B (H'=1.382, J'=0.5387) and A (H'=0.926, P=0, 3612). These results are in agreement with those of Ferraz et al (2010b), who also found greater diversity in the farthest point from the edge (1,000m), and are also corroborated by the studies of Esposito (1999) in the Amazon, who found …”
Section: Resultssupporting
confidence: 91%
“…This species was the most abundant at the midpoint, and was considered common and constant at all collection points, as also observed by Gadelha (2009) and Ferraz et al (2010b). Mello et al (2007) reported this species as the most abundant at the REBIO Tinguá, demonstrating that it is distributed in areas of the Atlantic Forest of Rio de Janeiro, especially in the range between 500 and 700m.…”
Section: Speciessupporting
confidence: 72%
See 3 more Smart Citations